Proyecto de Factibilidad para la Creación de una Empresa dedicada a la Producción y Comercialización de Pankeys de Banana en la Ciudad de Loja - Panamito Sánchez, María José (2016)
Currently in the city and province of Loja it is affected by a marked downturn in the productive field, being a barrier to sustainable development and that can compete with other provinces. That is why new generations of professionals have to make efforts to create small innovative companies, occupying the local workforce, with resources of the area and products that can go to market in optimal conditions. For these reasons, this project aims to assist with the implementation of a company that allows create some jobs, exploit the natural resources, creating economic value added and implement the acquired knowledge for the benefit of a society that needs to their new professionals are inserted in the productive and economic life. Hence the real need to produce goods and services, being entrepreneurs and facing the grave crisis facing our country, being convenient to carry out and execute our thesis project called "PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY DEDICATED TO THE PRODUCTION AND MARKETING PANKEYS oF BANANA iNtHEcITYoF LOJA. "the same that contributes to the development of this city. The full analysis of the project requires the completion of the following studies and analysis: market research, technical study, administrative and legal study, economic and financial study and finally the valuation of the project. 6 Market research for this survey was conducted both plaintiffs and suppliers, where three types of claims are quantified the potential demand that is 83% of yojanas families consume Pankey, while real demand is 31% since ever if they consume pankeys banana and effective demand is 86% of families who are willing to buy the product, and then determine the unsatisfied demand is 813,251 pankeys for the first year, the installed capacity is determined 100% for the first year and capacity utilization of the project is 100% for the first year alone. In the technical study the size of the plant is presented in relation to their installed and used capacity, macro and micro location and program production process flow was defined. Administrative and legal study of the company facilitates determining business group, organization and functions manuals. The company will be legally incorporated as a Limited Company, its minimum duration period of 5 years, its name: COMPANY produces and markets PAKEYS BANANA "MAJITO'S" Cia. Ltda. ". The mission will produce and market pankeys banana to meet quality and competitive prices demand of the city of Loja. Similarly hierarchical levels and organizational charts that began to work the company was determined also features manuals for the staff of the company was defined. 7 economic and financial study to learn about the project investment (investment in fixed assets $ 21,144; $ 1,170 Deferred tax assets and current assets or working capital $ 4529.17, with investment funding $ 26,843.17), budget revenue and expenses, cost analysis, break-even points and study and analysis of financial statements (income statement and cash flow). Finally the project evaluation was performed to establish the suitability of the project and its implementation for which the following indicators such as net present value of $ 10764.28 analyzed; Internal Rate of Return of 56.01%; Benefit Ratio Cost is $ 1.25 for every dollar invested company earns 25 cents; Capital Recovery period is 2 years, 8 months and 5 days; Sensitivity analysis indicates that the project supports an increase in costs of 5.04% for a total of 0.9984 and sensitivity analysis in the decrease in revenues of 4.03% danto a total of 0.997929, by which the project is feasible, the conclusions and recommendations so determined, accompanied by the bibliography consulted with their respective annexes.